REFLEKSI HUT LVRI DALAM PENGUATAN KETAHANAN SOSIAL DAN NILAI KEJUANGAN DI KOTA BENGKULU - Oktrina Syafriantini; Jasmani (Yayasan Pendidikan Literasi Borneo, 2025)
This study aims to examine the social contribution of LVRI Bengkulu Province in responding to disaster situations on the island of Sumatra in relation to the theme